Catalyst-free synthesis of low-temperature thermally actuated shape memory polyurethanes with modified biobased plasticizers. Issue 1 (21st December 2022) - Ali, Basharat; Atif, Muhammad; Perviaz, Muhammad; Irshad, Adnan; Abdullah, Muhammad; Mobeen, Muhammad Ahmad
Abstract : Recent years have seen research into developing specific application-based materials with particular components. Abstract : Recent years have seen research into developing specific application-based materials with particular components. Bio-based polyurethanes (PUs) with self-tightening effect through shape recovery at low temperature have been designed from sesame oil-based plasticizer (HSSO). Without using a catalyst, the produced plasticizer was used to create PU samples. In contrast, orcein-based PU has been created both with and without HSSO. The prepared samples have been analyzed through instrumental as well as chemical analyses for surface chemistry, thermal stability and morphology. The gel content and water absorption capacity of HSSO based PU samples has been observed to be 99.27% and 14.94%, respectively. Shape memory study of the PU samples revealed that HSSO-based PU showed fast shape recovery at 60 °C with shape recovery rate ( R r ) and shape fixing rate ( R f ) of 94.44% and 5%, respectively, in 150 seconds, whereas at 36 °C the sample showed 85% R r in 15 minutes with 93.1196 N force and 52.78% R r without force. Low-temperature thermal actuation and high water uptake highlight the prepared samples as suitable candidates for self-tightening structures in textile and biomedical fields.